Inter- and intra-observer reliability of the “Assessment of Motor Repertoire- 3 to 5 Months” based on video recordings of infants with Prader-Willi syndrome - Wang, Jun; Shen, Xiushu; Yang, Hong; Shi, Wei; Zhu, Xiaoyun; Gao, Herong; Yin, Huanhuan; Meng, Fanzhe; Wu, Yun (BMC pediatrics, 2022)
The "Assessment of Motor Repertoire-3 to 5 Months", which is a part of Prechtl's General Movements Assessment (GMA), has been gradually applied to infants with genetic metabolic disorders. However, there have been no studies on the application of the GMA for infants with Prader-Willi syndrome (PWS). The purpose of this study was to determine the inter- and intra-observer reliability of the assessment tool in a population of infants with PWS. This was a reliability and agreement study. This was a cross-sectional study with15 infants with PWS born at an average gestational age of 38 weeks. Standardized video recordings of 15 infants with PWS (corrected ages of 3 to 5 months) were independently assessed by three observers. Kappa and ICC statistics were applied in inter- and intra- observer reliability analyses. The overall reliability ICC values of the "Motor Optimality Score" (MOS) ranged from 0.84 to 0.98, and the pairwise agreement ranged between 0.86 and 0.95 for inter- observe reliability. In addition, ICC values for the MOS ranged between 0.95 and 0.98 for tester agreement in intra-observer reliability. Complete agreement reliability (100%) was achieved in the subcategories of "Fidgety Movements" and "Movement Character" for the inter- and intra-observer reliability. Moderate to high inter- and intra-observer reliability were found in the subcategories of "Repertoire of Co-Existent Other Movements", "Quality of Other Movements" and "Posture", with kappa values ranging between 0.63 and 1.00. There were high levels of inter-and intra-observer agreement in the "Assessment of Motor Repertoire-3 to 5 Months" for infants with PWS. It is possible to carry out standardized quantitative assessments of the motor performance of infants with PWS.